Produção de fitase por Rhizopus microsporus var. microsporus: purificação, caracterização bioquímica e aplicação - Sato, Vanessa Sayuri [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Biotechnological research, and the application of enzymes in combination with the use of genetic engineering has been carried out in microorganisms for the production of enzymes for industrial purposes. Among these enzymes, microbial phytases, which catalyze the hydrolysis of phytate (myo-inositol hexakisphosphate) to myo-inositol and inorganic phosphate, have been widely used in animal feed. In this context, the fungus R. microsporus var. microsporus was selected as a good producer of the phytase with higher production levels when grown on Biofilm Fermentation (FB) (261,30 U/mg), using sugarcane bagasse as carbon additional source. The morphology of biofilms on inert support was examined by SEM observing interconnected hyphae forming an ordered array in the presence of many channels which enables efficient exchange of nutrients and oxygen. The extracellular phytase was purified 4.18 fold with 4.78% recovery. A single protein band was obtained in 6% PAGE and confirmed by 12% SDS-PAGE as a single protein band with 34 kDa. The optimum temperature for activity was 55 °C and the optimum pH 4.5. It was completely stable at temperatures between 30 °C and 40 °C for 120 min had low pH with a residual activity of over 50% between pH 3.0 and 5.0 for 60 min. The enzyme was activated by Ca2+ and inhibited by Zn2+. The enzyme was able to hydrolyze sodium phytate with a Km=0.72 mM, Vmax= 94.55 U/mg of protein. The crude extract containing phytase was dried using Spray Dryer with different adjuvants. Soybean meal and corn meal allowed the best recovery of phytase activity 60% and 59.5%, respectively. Considering the use of these two adjuvants, the optimum pH of activity for phytase in the dry extract was 4.5 and 8.5, respectively, and the optimum of temperature of 45-50 °C. When used corn meal, the stability was maintained above 90% at pH 2.5-10.0 for 60 min. The dry phytase (corn meal) was applied to the feed...

A investigação biotecnológica acompanhada da aplicação das enzimas, combinada com o uso da engenharia genética tem sido realizada em micro-organismos para a produção de enzimas para fins industriais. Entre estas enzimas, as fitases microbianas, que catalisam a hidrólise do fitato (mio-inositol hexaquisfosfato) a mio-inositol e fosfato inorgânico, têm sido amplamente utilizadas na alimentação animal. Neste contexto, o fungo R. microsporus var. microsporus foi selecionado como bom produtor de fitases, com maiores níveis de produção encontrados na Fermentação por Biofilmes (FB) (261,30 U/mg), utilizando bagaço de cana de açúcar como fonte de carbono adicional. A morfologia do biofilme sobre suporte inerte foi analisada por MEV observando-se múltiplas hifas interligadas formando um conjunto ordenado na presença de inúmeros canais que permitem a troca eficiente de nutrientes e oxigenação. A fitase extracelular obtida foi purificada 4,18 vezes com recuperação de 4,78%, obtendo-se uma única banda de 34 kDa em SDS PAGE 12%. A temperatura ótima de atividade para a enzima purificada foi de 55ºC e o pH ótimo 4,5, sendo estável entre 30 °C e 40 °C por 120 min. Apresentou baixa estabilidade ao pH com atividade residual acima de 50% entre pH 3,0 e 5,0 por 60 min. A fitase foi ativada por íons Ca2+ e inibida por K+. A enzima foi capaz de hidrolisar fitato de sódio (Km de 0,72 mM e Vmax de 94,55 U/mg). O extrato bruto contendo fitase foi seco em Spray Dryer com diferentes adjuvantes (farelo de milho, farelo de soja, fubá, amido e maltodextrina). O farelo de soja possibilitou a maior recuperação da atividade fitásica (60%), assim como o fubá (59,5%). Considerando o uso destes dois adjuvantes, o pH ótimo de atividade para a fitase contida no extrato seco foi 4,5 e 8,5, respectivamente e a temperatura ótima de atividade de 45-50 °C. Quando utilizado fubá, a estabilidade foi mantida...
Keywords: Biotecnologia; Enzimas; Fungos filamentosos; Fermentação; Enzimas - Aplicações industriais; Fermentation